"عہدِ نبوی میں صحابیاتؓ کا دینی و سماجی مقام: ایک تحقیقی و تجزیاتی مطالعہ": “The Religious and Social Status of the Sahabiyāt in the Prophetic Era: An Analytical and Research-Based Study” (Al-Aasar, 2025)
The female Companions (Sahabiyāt), may Allah be pleased with them, occupy a distinguished position in Islamic history. In the early period of Islam, they not only demonstrated the highest standards of faith and piety but also played a prominent role in social, religious, and intellectual spheres. Being in close proximity to the Prophet Muhammad ﷺ, benefiting from his companionship, and receiving direct spiritual and ethical training from him, they became one of the strongest links in preserving and conveying the true understanding of faith, moral discipline, and practical conduct.In pre-Islamic Arabian society, women generally held an insignificant and marginalized status; however, Islam elevated the Sahabiyat by granting them honor, respect, rights, and responsibilities. They contributed effectively in various essential fields such as acts of worship, preaching and propagation of Islam, nurturing and educating children, participating in defensive efforts, providing medical aid, serving the Muslim community, and transmitting prophetic traditions. The Sahabiyat not only learned the foundational teachings of Islam but also conveyed them to future generations, and numerous juristic and hadith-related issues are understood through their narrated reports.Their contributions affirm that women held a fundamental, active, and respected role in shaping the Islamic society. For this reason, the study of the social and religious status of the Sahabiyat remains one of the significant and indispensable subjects in Islamic history and juristic tradition.